(Effort Increasing Learning Math Results through Cooperative Learning Method of Contextual Teaching and Learning Type in Students of Grade IV D SD Negeri 187 Pekanbaru): UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUIMETODE PEMBELAJARAN KOOPERATIF TIPE CONTEXTUAL TEACHING AND LEARNING PADA SISWA KELAS IV D SD NEGERI 187 PEKANBARU - Ningsih, Masneri (Perspektif Pendidikan dan Keguruan, 2018)
This research entitled "Efforts to Increase Mathematics Learning Outcomes Through Co-operative Learning Methods Contextual Teaching and Learning (CTL) Type in Grade IVd Elementary School 187 Pekanbaru". This research is to help students actively in finding ways of fast and precise settlement because students have difficulty in completing mathematis.The aim of this research is to improve student motivation in learning mathematics by using Cooperative Learning Method Type Contextual Teaching and Learning (CTL). Through this research the researcher tried to use Cooperative Learning Method of Contextual Teaching and Learning (CTL) type, through class action research of cycle model which includes planning, action implementation, observation, and reflection. The object of research is the students of grade IVB SD Negeri 187 Pekanbaru as many as 35 students. There are 2 cycles of learning process of student motivation. Each cycle consists of three stages of the meeting. The results obtained from this study show the student activity in the learning process better can be seen from the comparison of the results on the initial observation only 31% or 11 students who understand and the results are good. After the action, it can be seen in the first cycle increased to 63% (22) students who have completed, and the second cycle increased again reached 94% (33) students. Observation of student activities during the learning in cycle I can also be seen that is 2.44 (enough category), the cycle increased to 3.11 (good category). Likewise, observation of teacher activity from enough category (2.70) to good category (3.20). From the above explanation can be concluded that by using Cooperative Learning Methods Contextual Teaching and Learning (CTL) type can increase understanding of mathematics in constructing.